Kajian Pengaruh Pelumatan dan Penambahan Aktivator terhadap Produksi Biogas dari Sampah Sisa Makanan Restoran - Yuli Pratiwi; Angge Dhevi Warisaura (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2016)
This research to determine the effect of grinding and addition of activator on biogas production from restaurant foodwaste. Variations that were used in this study is grinded and not grinded. The second variations is by adding Green Phoskko® 0%, 0,1%, 0,25%, and 0,5%. Each variation is load 7 liters substrate. The study was conducted for 30 days. Parameters observed during the study are Chemical Oxygen Demand, pH, temperature, moisture content, Total Solid,Volatile Solid and volume of biogas in manometer. At the end of the study, biogas tested by Gas Chromatography to determine methane gas. The best reactor conditions on producing biogas is substrate with grinded materials and 0,25% of activator added. Materials that grinded has plenty volume of biogas and a fairly methane content.  It was showed in the highest cumulative volume of biogas produced by the reactor B1 with a volume of 202.41 mL, methane content 42 μL / 1mL and B3 with a volume of 171.666 mL, methane content 1,12 μL / 1mL. Grinded material and addition of activator has effect but not significant on the biogas production. This occurs because of an imbalance of anaerobic processes caused by the rate of pH decrease. Using of Green Phoskko® as an activator is not enough to provide optimal results.